Building Fault Tolerance Within Wsn- A Topology Model - M. Sai Rama Krishna; Ch. Jnana Gayathri; K. Laxmi Pallavi Rao (International Journal of Advances in Applied Sciences, 2018)
Wireless Sensor network plays a crucial role which helps in visualizing, processing, and analyzing the information wirelessly.  WSN is a network which consists of huge amount of sensor devices which are of low cost and low powered also known as sensor nodes. These type of networks are generally used in real time applications such as monitoring of environmental conditions, militaries, industries etc.,.but the problem that exists in WSN is may be due to different failures such as node failure, link failure, sink failure, interference, power dissipation and collision. If these faults are unable to handle then the desired network criteria’s may not be reached properly which results in inefficiency of the network. So, the main idea behind the investigation is to form a different networking topology which works in the event of failure